Computational Social Science: Toward a Collaborative Future - Wallach, Hanna (Computational Social Science: Discovery and Prediction, 2016)
Fifteen years ago, as an undergraduate computer science student in the UK, I read a popular science article (Matthews, 1999) proﬁling the research of my now colleague, Duncan Watts. This article, about the science of small-world networks, changed my life. To understand why, though, it’s necessary to know that in the UK, there is (or at least was during the 1980s and 1990s) a profound ”them-versus-us” split between the STEM1 ﬁelds and all other disciplines. This split is ampliﬁed or perhaps even caused by the fact that people specialize very young — choosing, at age ﬁfteen or sixteen, whether they will ever take another math course or write another essay again. I, like every one else in my degree program, had chosen STEM, but my decision hadn’t been easy — I had also wanted to study the social sciences. The article about Duncan’s research changed my life because it had never before occurred to me that that math and computers could be used to study social phenomena. For the ﬁrst time, I realized that rather than studying either computer science or the social sciences, perhaps I could study both. This, then, became my motivating goal.